[En]gendering the norms of customary inheritance in Botswana and South Africa. Issue 2 (3rd May 2016) - Kingwill, Rosalie
ABSTRACT: The article responds to the article by Weinberg in this issue. She traces the trajectory of court hearings concerning the contested inheritance of land in Botswana, which, after several prior judgements eventually resulted in a positive outcome for the woman litigants. I acknowledge the author's key argument, which concerns the impact of power relations on the construction of customary law and the reproduction of knowledge in the courts. Certain versions of "custom" were promoted and others stilled to the disadvantage of women. I argue that the normative patterns of landholding are indeed gendered, but do not result in a binary structure of men and women. "Gender" should be disaggregated to take into account a range of status criteria within and across the categories of male and female in order to understand the differential impact of social relations on the outcomes of property struggles. The normative lines of property transmission frequently follow a logic of "family property" that allows for qualifying women to rights of property. Family property has vastly different social and legal consequences to private, individualised property rights. The corollary is that it is misleading to speak of the processes of succession to rights of access to, and control of customary property in terms of one-to-one "inheritance" of land. The concept of "living law" inadequately reflects these social dynamics.